Effects of inspiratory muscle training in professional women football players: a randomized sham-controlled trial - Archiza, B.; Kuguimoto Andaku, D.; Rossi Caruso, F. C.; Bonjorno Jr., J. C.; de Oliveira, C. R.; Ricci, P. A.; do Amaral, A. C.; Mattiello, S. M.; Libardi, C. A.; Phillips, S. A.; Arena, R.; Borghi-Silva, A. (Journal of Sports Sciences, 2018)
This study was conducted to determine the effects of inspiratory muscle training (IMT) on respiratory and peripheral muscles oxygenation during a maximal exercise tolerance test and on repeated-sprint ability (RSA) performance in professional women football players. Eighteen athletes were randomly assigned to one of the following groups: SHAM (n = 8) or IMT (n = 10). After a maximal incremental exercise test, all participants performed (on a different day) a time-to-exhaustion (Tlim) test. Peripheral and respiratory muscles oxygenation by near-infrared spectroscopy, breath-by-breath ventilatory and metabolic variables, and blood lactate concentration were measured. The RSA test was performed on a grass field. After a 6 week intervention, all athletes were reevaluated. Both groups showed increases in inspiratory muscles strength, exercise tolerance and RSA performance, however only the IMT group presented lower deoxyhemoglobin and total hemoglobin blood concentrations on intercostal muscles concomitantly to an increased oxyhemoglobin and total hemoglobin blood concentrations on vastus lateralis muscle during Tlim. In conclusion, these results may indicate the potential role of IMT to attenuate inspiratory muscles metaboreflex and consequently improve oxygen and blood supply to limb muscles during high-intensity exercise, with a potential impact on inspiratory muscle strength, exercise tolerance and sprints performance in professional women football players.